Fixed vs countercyclical LTV ratio: the effectiveness of macroprudential policy for a small open economy - Mohd Zin, Mohd Taufiq (2023)
In this paper, I develop a dynamic stochastic general equilibrium (DSGE) model for a small open economy. The model includes a housing market and aims to study the effectiveness of a macroprudential policy, namely the loan-to-value (LTV) ratio, in taming the financial and business cycles. This paper compares the implementation of LTV under fixed and countercyclical rules. A countercyclical LTV rule is more effective for a closed economy in taming both the financial and business cycles. However, for a small open economy, while a countercyclical LTV rule is more effective in taming the financial cycle, the impact on the business cycle is indifferent under both LTV rules. This phenomenon is mainly explainable by the final good producers’ ability to change their composition between domestic and imported goods in their productions. This reflects the expenditure switching channel between foreign and domestic goods. I also explore the benefit of targeting the nominal exchange rate by the central bank or augmenting the countercyclical LTV rule by including the movement in the nominal exchange rate. There seems to be a policy trade-off between achieving financial and output stabilisation that the central bank needs to consider when the nominal exchange rate is included in the monetary policy or countercyclical LTV rules. In both cases, more stabilisation in output is achieved at the expense of more volatility in the financial cycle